"Snooping" as a Distinct Parental Monitoring Strategy: Comparisons With Overt Solicitation and Control. (26th March 2015) - Hawk, Skyler T.; Becht, Andrik; Branje, Susan
Abstract : Parents can use solicitation (asking questions) and control (disclosure rules) to obtain information about adolescents, but only if youths comply. Snooping might uncover additional information, but also strongly violates privacy expectations. Three studies of parents and adolescents examined distinctions between snooping, solicitation, and control. Differences existed in terms of factor structure and frequency (Studies 1–2), links to perceived invasion (Study 1), correlations with problematic communication, behavior, and relationships (Study 2), and parent–adolescent (dis)agreement about acceptability (Study 3). Snooping is a relatively infrequent monitoring behavior, compared to solicitation and control, but appears to be a stronger indicator of problems in adolescent and family functioning. We discuss implications regarding the necessity and appropriateness of particular parental monitoring behaviors.